2008
DOI: 10.1093/jxb/ern054
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of C4 photosynthesis intermediate exchange between Kranz mesophyll and bundle sheath cells in grasses

Abstract: C(4) photosynthesis involves cell-to-cell exchange of photosynthetic intermediates between the Kranz mesophyll (KMS) and bundle sheath (BS) cells. This was believed to occur by simple diffusion through plentiful plasmodesmatal (PD) connections between these cell types. The model of C(4) intermediates' transport was elaborated over 30 years ago and was based on experimental data derived from measurements at the time. The model assumed that plasmodesmata occupied about 3% of the interface between the KMS and BS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 58 publications
0
36
0
Order By: Relevance
“…In addition to the C 4 enzymes, C 4 photosynthesis evolution necessitated rearrangements of chloroplast envelope proteins (Bräutigam et al, 2008). Furthermore, transport of C 4 intermediates between M and BS cells is probably not performed through simple diffusion, which suggests that other, unidentified, mechanisms exist (Sowinski et al, 2008), which may be yet another C 4 -specific adaptation.…”
mentioning
confidence: 99%
“…In addition to the C 4 enzymes, C 4 photosynthesis evolution necessitated rearrangements of chloroplast envelope proteins (Bräutigam et al, 2008). Furthermore, transport of C 4 intermediates between M and BS cells is probably not performed through simple diffusion, which suggests that other, unidentified, mechanisms exist (Sowinski et al, 2008), which may be yet another C 4 -specific adaptation.…”
mentioning
confidence: 99%
“…This indicates that a rapid diffusion between BSCs and MCs can potentially be supported. However, a recent theoretical analysis based on plasmodesmatal structure and its diffusional properties showed that the required metabolite gradient between BSCs and MCs to support observed rate of C4 photosynthetic CO 2 uptake should be at least three orders of magnitude higher than experimentally measured (Sowinski et al, 2008). Recent and historical measurement indicated that unidirectional transport of fluorescent protein through plasmodesmata exists in unique surfaces (Arisz, 1969;Christensen et al, 2009), which suggested that active transport or accelerated diffusion of small molecules of certain size may occur through plasmodesmata.…”
Section: The Effects Of Varying Plasmodesmata Length On C4 Photosynthmentioning
confidence: 99%
“…S2). In the simulation, the same permeability was assumed for both T3P and PGA (C3P [compounds containing three carbons and a phosphate group]), because they have the same diffusion properties (Sowinski et al, 2008). At a given permeability to C3P transport, increasing the permeability of plasmodesmata to CO 2 first increases and then decreases A (Fig.…”
Section: The Influence Of Intracellular and Intercellular Metabolite mentioning
confidence: 99%
See 1 more Smart Citation
“…Their localization necessitates the presence of transport proteins which connect the reactions of the C 4 cycle to the cytosol [16]. In turn, the cytosols of the PEPC containing mesophyll tissue and the RubisCO containing bundle sheath tissue share a symplastic connection [17][18][19][20]. Molecular identification of the transport proteins lags behind identification of the enzymes.…”
mentioning
confidence: 99%